The Effect of Technological Innovation on Business Sustainability Based on Society 5.0 Dimension: New Decision Making Methods - Fuad, Muhammad; Darusman, Darusman; Kurniasari, Fita; Agung Madepo, Mahardika (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This study aims to analyze the relationship between technological innovation, business decision-making, and sustainability in the context of Society 5.0. Mixed methods approaches are used to gain a deep and diverse understanding of these complex interactions. The data collection was done through online surveys and in-depth interviews. Quantitative analysis uses regression to examine the relationship between technological innovation adoption and sustainable business decision-making. Qualitative analysis was performed using a thematic approach to interview transcripts. The results of the analysis show that there is a positive and significant correlation between the level of technological innovation adoption and the effectiveness of sustainable business decision-making. Qualitative results reveal stakeholder views on the impact of technological innovation on business implementation and decision-making challenges. The conclusion of this study highlights the important role of technological innovation in achieving sustainable business goals, providing guidance for the development of adaptive business strategies in an age of technological change and society.